‘Fine, Invisible Threads’: Schopenhauer on the Cognitively Mediated Structure of Motivation - Sean T. Murphy (Journal of Modern Philosophy)
The central claim of Schopenhauer’s account of human motivation is that ‘cognition is the medium of motives’. In light of motivation’s cognitively mediated structure, he contends that human beings are caused to act by ‘mere thoughts’, what he refers to metaphorically as ‘fine, invisible threads’. Despite this avowedly intellectualist handling of the subject, some commentators remain convinced that Schopenhauer is best read as accepting the ‘Humean truism’ that reason alone never motivates; rather, motivation always has its source in desire together with instrumental belief (Young 1987). Here, I raise some doubts for the Humean reading by arguing that it does not take sufficient account of the transformative effects of cognitive mediation, effects which support cases of non-desiderative motivation. I argue in particular that Schopenhauer permits cases of motivation by the essentially cognitive states of imagination and recognition. Tracing this intellectualist strand in Schopenhauer’s view of motivation has two important results. First, it unmasks an important structural role for Besonnenheit (reflectiveness) in his account of practical agency, thereby revealing a unified thread running throughout his system; second, we alight on a possible ‘expressivist’ picture of his account of motivation, something it shares with his broader theory of action.